The poisonous solicitor the true story of a 1920s murder mystery - Bates, Stephen 1958- (Icon Books Ltd, 2023)
In 1922, Major Herbert Armstrong, a Hay-on-Wye solicitor, was found guilty of, and executed for, poisoning his wife, Katharine, with arsenic. Armstrong's case has all the ingredients of a classic murder mystery, from a plot by Agatha Christie or Dorothy Sayers (indeed some aspects of his story appear in Sayers' Unnatural Death). It is a near-perfect whodunnit. One hundred years later, Agatha Award-shortlisted Stephen Bates examines and retells the story of the case, evoking the period and atmosphere of the early 1920s, a time of newspaper sensationalism, hypocrisy and sanctimonious morality
"First published in the UK by Icon Books Ltd in 2022."--title page verso
Keywords: Geschichte 1921; Mord; Wales; Armstrong, Herbert Rowse / -1922 / Trials, litigation, etc; Armstrong, Katharine / -1921 / Death and burial; Murder / Wales / Hay / History / 20th century; Poisoning / Great Britain / Case studies; Trials (Murder) / Wales / History; Wales / History / 20th century; Procès (Meurtre) / Pays de Galles / Histoire; Pays de Galles / Histoire / 20e siècle; Armstrong, Herbert Rowse / -1922 / https://id.oclc.org/worldcat/entity/E39PBJtRFTdwQBbBmKF9gVpQMP; Armstrong, Katharine / -1921; Death and burial of a person; Murder; Poisoning; Trials (Murder); Great Britain / https://id.oclc.org/worldcat/entity/E39PBJdmp7p3cx8hpmJ8HvmTpP; Wales / https://id.oclc.org/worldcat/entity/E39PBJqjY9ywKtRXDhDV77yyBP; Wales / Hay / https://id.oclc.org/worldcat/entity/E39PBJhxry6bt94vMHvFpfycfq; 1900-1999; Case studies; History; Trials, litigation, etc